Machine Intelligence (International Journal of Scientific Research and Management (IJSRM), 2023)
Decision making is the most important part in everyday life. We make numerous decisions throughout the day from small to big decisions. These decisions involve choosing which food to eat to choosing in which bank to invest money. Another word for decision making is making choices. In [1], artificial intelligence was demonstrated as solutions to solve problems. At a more general level, we need to make decisions in order to solve problems. This paper is about that. It illustrates a simple concept to solve problems.